2023
DOI: 10.1002/ijc.34620
|View full text |Cite
|
Sign up to set email alerts
|

Clonal expansion of intra‐epithelial T cells in breast cancer revealed by spatial transcriptomics

Abstract: The spatial distribution of tumor‐infiltrating lymphocytes (TIL) predicts breast cancer outcome and response to systemic therapy, highlighting the importance of an intact tissue structure for characterizing tumors. Here, we present ST‐FFPE, a spatial transcriptomics method for the analysis of formalin‐fixed paraffin‐embedded samples, which opens the possibility of interrogating archival tissue. The method involves extraction, exome capture and sequencing of RNA from different tumor compartments microdissected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…Found immune repertoires of intra-epithelial T and B cells were consistently less diverse and more clonal than those in stroma. (Romanens et al 2023a ) Breast cancer ‘Spatial transcriptomics’ 1 sample Original 2016 publication in Science , demonstrated ST method with arrayed oligonucleotides with positional barcordes. ST applied to mouse brain and human breast cancer tissue containing DCIS and invasive components.…”
Section: Spatial Transcriptomics In Solid Tumors: What We’ve Learned ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Found immune repertoires of intra-epithelial T and B cells were consistently less diverse and more clonal than those in stroma. (Romanens et al 2023a ) Breast cancer ‘Spatial transcriptomics’ 1 sample Original 2016 publication in Science , demonstrated ST method with arrayed oligonucleotides with positional barcordes. ST applied to mouse brain and human breast cancer tissue containing DCIS and invasive components.…”
Section: Spatial Transcriptomics In Solid Tumors: What We’ve Learned ...mentioning
confidence: 99%
“…They showed that axillary lymph nodes transform into a tumor-like state with T-cell exhaustion, as well as a decrease in B cells and neutrophils (Mao et al 2023 ). Additionally, based on a laser capture microdissection approach, the immune repertoires of intraepithelial T and B cells have been shown to be consistently less diverse and more clonal than those of stromal T and B cells (Romanens et al 2023b ). A comparative analysis of samples from African American women and Caucasian women revealed race-associated differences in regions with immune-rich infiltrates (Bassiouni et al 2023 ).…”
Section: Spatial Transcriptomics In Solid Tumors: What We’ve Learned ...mentioning
confidence: 99%